2021
DOI: 10.3389/fpls.2021.637488
|View full text |Cite
|
Sign up to set email alerts
|

Developing Climate-Resilient, Direct-Seeded, Adapted Multiple-Stress-Tolerant Rice Applying Genomics-Assisted Breeding

Abstract: There is an urgent need to breed dry direct-seeded adapted rice varieties in order to address the emerging scenario of water–labor shortage. The aim of this study was to develop high-yielding, direct-seeded adapted varieties utilizing biparental to multiparental crosses involving as many as six different parents in conventional breeding programs and 12 parents in genomics-assisted breeding programs. The rigorous single plant selections were followed from the F2 generation onwards utilizing phenotypic selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Different crossing strategies (Additional file 2 : Figure S9) single, complex, double, and backcrosses have been used by the rice breeders to integrate these QTLs into the elite genetic backgrounds and develop the new breeding lines. Diverse materials, including landraces, and donors have been extensively used to diversify the gene pool and develop climate-resilient varieties (Sandhu et al 2021 ; Yadav et al 2021 ). However, this strategy of diversifying the elite gene pool with limited focus on recurrent selection and early re-cycling of high-value breeding lines may have limited genetic gain to a large extent and has not been sufficient to maintain the higher genetic gains over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different crossing strategies (Additional file 2 : Figure S9) single, complex, double, and backcrosses have been used by the rice breeders to integrate these QTLs into the elite genetic backgrounds and develop the new breeding lines. Diverse materials, including landraces, and donors have been extensively used to diversify the gene pool and develop climate-resilient varieties (Sandhu et al 2021 ; Yadav et al 2021 ). However, this strategy of diversifying the elite gene pool with limited focus on recurrent selection and early re-cycling of high-value breeding lines may have limited genetic gain to a large extent and has not been sufficient to maintain the higher genetic gains over time.…”
Section: Discussionmentioning
confidence: 99%
“…Under this project, imperative efforts were made to incorporate the major drought-tolerant QTLs ( qDTY1.1, qDTY2.1, qDTY2.2, qDTY3.1, qDTY4.1, qDTY12.1 qDTY6.3, etc . ) into the background of the mega rice varieties like IR64, Swarna, and TDK-1, which led to the development of several high yielding drought-tolerant rice varieties (Bernier et al 2007 ; Venuprasad et al 2009 ; Vikram et al 2011 ; Mishra et al 2013 ; Yadaw et al 2013 ; Sandhu et al 2014 , 2019 , 2021 ; Kumar et al 2014 , 2020 ; Henry et al 2015 , 2019 ; Dixit et al 2017 , 2020 ; Sandhu and Kumar 2017 ; Bhandari et al 2020 ; Majumder et al 2021 ; Yadav et al 2021 ). The most popular drought-tolerant rice varieties include—DRR dhan 42, CR Dhan 801, Sahbhagi dhan in India, Sukha dhan 4, Bahuguni dhan 11 in Nepal, and Katihan 2, Katihan 3, Sahod Ulan 15, Sahod Ulan 19 in the Philippines, Yaenelo 4 in Myanmar, MPTSA and ATETE in Malawi, CAR 14 in Cambodia, and BRRI Dhan66, BRRI Dhan 71 in Bangladesh ( https://strasa.irri.org/varietal-releases/drought ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, enhanced CF demarcates a plant's capabilities to withstand drought stress effectively. Furthermore, two multiparent conventional bred lines namely, IR 115844-B-B-281-1-2 and IR 115844-B-342-1-1-1 present in the selected panel have been reported to yield more than 7000 kg/ha under dry direct-seeded conditions, with higher yields under non-stress and reproductive stage drought stress conditions (Sandhu et al 2021). In our study, these lines showed the breeding values between 3200 to 3368.14, which form a valuable resource for the breeding programs to be utilized for drought-prone areas with major cultivation under dry seeded conditions having limited water and labor availability.…”
Section: Development Of Breeding Panel As the Future Breeding Resourcementioning
confidence: 99%
“…S8) single, complex, double, and backcrosses have been used by the rice breeders to integrate these QTLs into the elite genetic backgrounds and develop the new breeding lines. Diverse materials, including landraces, and donors have been extensively used to diversify the gene pool and develop climate-resilient varieties (Sandhu et al 2021). However, this strategy of diversifying the elite gene pool with limited focus on recurrent selection and early re-cycling of high-value breeding lines may have limited genetic gain to a large extent and has not been sufficient to maintain the higher genetic gains over time.…”
Section: Development Of Breeding Panel As the Future Breeding Resourcementioning
confidence: 99%
See 1 more Smart Citation